Search for top squark pair production in compressed-mass-spectrum scenarios in proton-proton collisions at root s=8 TeV using the alpha(T) variable - Khachatryan, V. (2017)
An inclusive search is performed for supersymmetry in final states containing jets and an apparent imbalance in transverse momentum, (p) over right arrow (miss)(T),due to the production of unobserved weakly interacting particles in pp collisions at a centre-of-mass energy of 8 TeV. The data, recorded with the CMS detector at the CERN LHC, correspond to an integrated luminosity of 18.5fb(-1). The dimensionless kinematic variable alpha(T) is used to discriminate between events with genuine (p) over right arrow (miss)(T)associated with unobserved particles and spurious values of (p) over right arrow (miss)(T) Tarising from jet energy mismeasurements. No excess of event yields above the expected standard model backgrounds is observed. The results are interpreted in terms of constraints on the parameter space of several simplified models of supersymmetry that assume the pair production of top squarks. The search provides sensitivity to a broad range of top squark ((t) over tilde) decay modes, including the two-body decay (t)over tilde> -> c (chi) over tilde (0)(1),where c is a charm quark (chi) over tilde (0)(1) and is the lightest neutralino, as well as the four-body decay (t)over tilde> -> bf (f) over bar' (chi) over bar (0)(1),where b is a bottom quark and f and (f) over bar' are fermions produced in the decay of an intermediate off-shell W boson. These modes dominate in scenarios in which the top squark and lightest neutralino are nearly degenerate in mass. For these modes, top squarks with masses as large as 260 and 225 GeV are excluded, respectively, for the two-and four-body decays. (C) 2017 The Author. Published by Elsevier B.V.